Uterine Microbiology of Healthy Cows and Cows That Develop Uterine Disease - Klibs N. Galvão (EDIS)
The dairy cow is unique because virtually all cows are infected with bacteria right after calving. A recent study that used metagenomic analysis to characterize the uterine flora in healthy and metritic cows observed that most clone sequences from the metritic cows were from the phylum Fusobacteria. This 4-page fact sheet summarizes what is known about the pathogenic bacteria associated with metritis and endometritis. Written by Klibs N. Galvão and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, January 2012.